A study on the crustal movement in the Nepal Himalayas (Journal of Nepal Geological Society, 1982)
Under the circumtances, basic data on the crustal movement of the Nepal Himalayas are most necessary. The upheaval process of some ten million years from Tertiary to present should be understood by the analysis of the kinematics being constructed by the time dependence process of the three dimensional architecture of the mountains. In other words, the crustal movement of 107-8 years should be revealed by geological method, that of 104-5 years by geomorphological method, and 100-2 years by geodetic method. These data should be integrated to elucidate the problem.The geological investigations of the Nepal Himalayas have been conducted by the scientists of the Tethys Society and various universites in Japan since 1962. Some of the main achievements of these investigations have been published in the "Geology of the Nepal Himalayas" (edited by S. Hashimoto, 1973).